2011
DOI: 10.1002/jbm.a.33082
|View full text |Cite
|
Sign up to set email alerts
|

Controlling neurite outgrowth with patterned substrates

Abstract: In vivo, neurons form neurites, one of which develops into the axon while others become dendrites. While this neuritogenesis process is well programmed in vivo, there are limited methods to control the number and location of neurite extension in vitro. Here we report a method to control neuritogenesis by confining neurons in specific regions using cell resistant poly(oligoethyleneglycol methacrylate-co-methacrylic acid (OEGMA-co-MA)) or poly(ethyleneglycol-block-lactic acid) PEG-PLA. Line patterned substrates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…In this study PC12 cells and their neurite outgrowths were confined to collagen-I, patterned as lines, resulting in cells with a bipolar morphology in which only two neurites extended along the collagen-I pattern. Similar studies (Yang, Co et al 2011, Cai, Zhang et al 2012) in which PC12 cells were confined to a line pattern showed that decreasing widths, of similar dimensions to our 20 µm wide collagen-I patterns, led to an increase in cell alignment. Furthermore, widths of similar dimensions exhibited the formation of one or two neurites, as opposed to larger widths which exhibited formation of more than two neurites (Mahoney, Chen et al 2005).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In this study PC12 cells and their neurite outgrowths were confined to collagen-I, patterned as lines, resulting in cells with a bipolar morphology in which only two neurites extended along the collagen-I pattern. Similar studies (Yang, Co et al 2011, Cai, Zhang et al 2012) in which PC12 cells were confined to a line pattern showed that decreasing widths, of similar dimensions to our 20 µm wide collagen-I patterns, led to an increase in cell alignment. Furthermore, widths of similar dimensions exhibited the formation of one or two neurites, as opposed to larger widths which exhibited formation of more than two neurites (Mahoney, Chen et al 2005).…”
Section: Discussionsupporting
confidence: 87%
“…Despite the use of BSA coating, however, very small numbers of cells were found attached to regions without collagen; those that remained after washing showed only limited growth in all directions. Although BSA was used in this study, it is possible to use other commonly used coatings to prevent cell attachment such as PLL or PEG (Yang, Co et al 2011, Poudel, Lee et al 2013). This procedure allowed the PC12 cells to be patterned on large surface areas, up to 13 × 10 mm 2 in our case (Figure 4c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Axon alignment and outgrowth is increased as a response to greater depths of the grooves because cell bodies are restricted to the grooves, avoiding neuronal crossing between grooves. Several studies have stated that an optimal groove width of 20 μm enhances neurite extension and achieves a bipolar structure oriented in the direction of the grooves and with a significant reduction in neurite branching [119]. Other investigations gave similar results using stem cells and neuronal lines, including human neural stem cells [120] and PC-12 cells [121,122].…”
Section: Topographical Cuesmentioning
confidence: 78%
“…77 The spatial neurite extension of cortical neurons was also controlled by confining the shape of cell-adhesive regions of poly-D-lysine with cell-resistant PEG materials (e.g., PEG-PDLA) lined up as barriers. 78 Interestingly, glass surfaces patterned with PEG dimethacrylate (PEGDMA) micro-wells promoted the differentiation of preadipocytes with increasing lipid accumulation, though it significantly increased the contact angle and decreased surface energy, making the surface less cell adhesive than unpatterned glass. 79…”
Section: Decoupling Polymer Propertiesmentioning
confidence: 99%